多级NGW型行星齿轮传动的设计 - 洪雷; 李学明; 王进戈 (Jixie Chuandong, 2011)
The characteristics of NGW planetary gear sets widely used in WTGs are introduced.With the design of pitch reducer for 1.5 MW WTGs,some of the key design principles and general experienced conclusions for the important and difficult points of multi-stage planetary gear transmission are given.Gear tooth strength of the weak stage is analyzed and the tooth face shape is optimized by the application of virtual prototyping tools Romax Designer.By the use of uniform load mechanism,the efficiency of the multi-stage planetary gear transmission is improved.Furthermore,the reasonability of design is proved by the prototype testing.